2018
DOI: 10.3991/ijim.v12i2.8118
|View full text |Cite
|
Sign up to set email alerts
|

Improving Pre-hospital Care of Road Traffic Accident's Victims with Smartphone Technology

Abstract: <p class="0abstract">One of the most causes to lose millions of lives around the world is Road Traffic Accidents (RTAs). According to the world health organization (WHO) report, 1.25 million people are killed each year as a result of RTAs, 20 to 50 million people were injured, and the number of killed people by RTAs is expected to increase further by 2020. The recent studies conclude that patient survival during a health emergency situation depends on the effective pre-hospital healthcare services, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Thus, the first aid crew arriving first at the scene should be provided with oxygen. One recent study conducted in Tabuk, KSA, indicated that pre-hospital care for crash victims could be enhanced using mobile phone smart technologies by proper coordination with nearby available facilities/services [99].…”
Section: Emergency Medical Care Units For Victimsmentioning
confidence: 99%
“…Thus, the first aid crew arriving first at the scene should be provided with oxygen. One recent study conducted in Tabuk, KSA, indicated that pre-hospital care for crash victims could be enhanced using mobile phone smart technologies by proper coordination with nearby available facilities/services [99].…”
Section: Emergency Medical Care Units For Victimsmentioning
confidence: 99%
“…Haghparast et al, in a study on the possibilities and barriers to providing care to patients in Iran, determined that communication and the availability of equipment and resources were considered one of the most important components in reducing the arrival time of the rescue unit to the accident site (1). Communication has changed tremendously in recent years which has led to the development and improvement of the quality of pre-hospital emergency services (3). The World Health Organization states that the use of electronic and telemedicine services and the provision of emergency medical equipment with high-tech equipment is one of the potential solutions to eliminate and reduce inequalities in the distribution of healthcare and facilitate equitable treatment for patients around the world (11).…”
Section: Introductionmentioning
confidence: 99%
“…This technology provides easy access to the geographical location of aid workers and provides the opportunity to support emergency services and improve coordination to manage as many patients as possible (3). Pre-hospital emergency operations staff can use this program to interact with the command room and exchange information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation